Europeización del Bienestar y activación - Serrano Pascual, Amparo; Moreno, Luis (Política y Sociedad, 2008)
The process of Europeanization implies a confluence of resources, social representations and outputs by the EU member states. This is mainly due to the sharing of ideas and values, to structural economic harmonisation, and to institutional system-building. This article deals with welfare developments concerned with the European social model (ESM) in contemporary times. Such and related terms, together with other conceptual premises, are analysed in the introductory section, followed by a discussion on the various European welfare regimes. Activation is single out as the new paradigm assumed in various degrees and understandings by all the European countries. However, different perspectives can be identified on the activation paradigm, a task carried out in the third and fourth sections. The ‘Open Method of Co-ordination’ (OMC) serves as main element of reference and comparison. Among other concluding remarks, it is argued that the general process of Europeanization is conditioned by an ambivalent perception of activation as enhancing regulatory principles and solidarity or as empowering citizens by means of welfare individualization.